In-vitro cultural, nutritional, antioxidant and antimicrobial potential of Macrolepiota procera and Amanita caesaria: A rare mushroom from Madhya Pradesh, India under Submerged Culture Condition - Rajoriya, Ashutosh; Dhok , Pushpanjali; Gawali, Kevin (Mushroom Research, 2022)
Macrolepiota procera and Amanita caesaria are the rarely accepted mushrooms among the society even if both are well known for their therapeutic properties. Present findings are focused on their in-vitro growth performance, colony characteristics, nutritional properties, antioxidant and antimicrobial activity under submerged culture conditions. The mushroom fruit bodies were collected from the different forest divisions of Madhya Pradesh and cultured. Malt extract broth was best suited medium for both Macrolepiota procera and Amanita caesaria. Biochemical studies in the mushroom mycelia grown in malt extract revealed a very good range of phyto-chemicals, which are considered as strong therapeutic agents. In addition, radical scavenging activity in the culture broth was assayed and highest activity was also recorded in malt extract media. Macrolepiota procera exhibited 55.74 % while Amanita caesaria exhibited 61.22 % of free radical scavenging activity. Malt extract medium thus proved to be the best medium for the culturing as well as for the production of antioxidants by both the mushroom species selected. In case of Antioxidant activity boiled water extract proven to be better than methanolic extract.